Improvement of the Sintered Surface and Bulk of the Product Via Differentiating Laser Sintering (Melting) Modes; IOP Conference Series: Materials Science and Engineering; Vol. 142 : Innovative Technologies in Engineering - Saprykina N. A. Natalia Anatolyevna; Saprykin A. A. Aleksandr Aleksandrovich; Arkhipova D. A.; Borovikov I. F. (2016, 2016)
Title screen